Physical Properties of Aerosol Internally Mixed With Soot Particles in a Biogenically Dominated Environment in California. Issue 20 (29th October 2018) - Sharma, Noopur; China, Swarup; Bhandari, Janarjan; Gorkowski, Kyle; Dubey, Manvendra; Zaveri, Rahul A.; Mazzoleni, Claudio
Abstract: Atmospheric soot particles are often internally mixed with organic aerosol. The geometric distribution of the mixing components affects the soot particles' radiative properties. Here we present an electron microscopy analysis of particles collected in a biogenically dominated environment to understand how the viscosity of secondary organic aerosol relates to various soot mixing configurations. The shape of particles impacting on a substrate deforms according to their viscosity. We use the aspect ratio of individual particles determined by tilt angle imaging to classify them into low, intermediate, and high viscosity groups. Ninety percent of the particles partially engulfing soot belong to the intermediate viscosity regime. In contrast, the highly viscous organic aerosol remains externally mixed with or attaches to the surface of soot particles. Our results link the viscosity of organic aerosol with the mixing configuration of soot‐containing particles. Including these findings in mixing state models could improve estimates of the soot radiative forcing. Plain Language Summary: In this study, we investigate the link between the viscosity of secondary organic aerosol internally mixed with soot and the geometric configuration of the mixture. The motivation of the study is that the details of the mixture geometry determine the optical properties and the radiative forcing of soot‐containing particles. We use tilt‐angle scanning electron microscopy and find that organic material of intermediate viscosity often partially engulfs soot, while highly viscous organic aerosol attaches to the soot surface or remains externally mixed. The implications of the study are that numerical models might be able to better predict the radiative forcing of soot‐containing particles by accounting for the viscosity of organic aerosols based on their chemical composition and the environmental conditions, such as temperature and relative humidity. Key Points: Tilt angle electron microscopy provides information about the viscosity of organic aerosol Various internal mixing configurations of soot with host particles are examined The viscosity of organic aerosol relates to the internal mixing configuration of soot‐containing particles